A review on the identification and analysis of heavy metals in herbs using inductively coupled plasma mass spectrometry (ICPMS) - Amid, Malaysia; Laili, Iffah Nadia (2019)
Pollution becomes a severe issue in Malaysia due to the economic development and increased industrialisation activities, with the most recent case of chemical residues that polluted the Kim Kim River, at Pasir Gudang, Johor in March this year. This serious situation may cause by various contaminants such as pesticides or chemical fertiliser for water pollution, smoke and emission from automotive for air pollution and solid waste for land pollution. The application of pesticides and chemical fertilisers in agriculture industry lead to heavy metal contamination in herbs products, thus reduces health quality. The government authority involves in monitoring and preventing the incidences uses suitable method in detecting the heavy metal contaminant such as Atomic Absorption Spectrophotometry (AAS), Inductively Coupled Plasma (ICP), and Neutron Activation Analysis (NAA). Other than that, Flame Atomic Absorption Spectrometry (FAAS), Energy Dispersive X-ray Fluorescence (EDXRF), and Electrothermal Atomic Absorption Spectrometry (ETAAS) were also used. Among the methods, ICPMS has been the most chosen and a convenience method to detect heavy metal contamination.